PELATIHAN BAGI GURU SD MENGAPLIKASIKAN MUATAN PENDIDIKAN LITERASI HUMANIS UNTUK MEMBENTUK TUNAS PANCASILA - Dina Mardiana; Kuswari; Simpun (LPPM Universitas Palangka Raya, 2023)
The Lecturer Program for Assisting Excellent Human Resources (PDPSU) is one of the schemes in the community service activity (PKM) at the university which was carried out by the FKIP Lecturer Team from the University of Palangka Raya (UPR). This PDPSU activity was carried out using blended learning to provide training to collaborator teachers at SDN-2 Panarung, Kota Palangka Raya. The purpose of this PKM-PDPSU activity is to train and assist teachers at SDN-2 Panarung in applying humanist literacy education to the content of language learning materials in the primary school. This is done to build Pancasila-uphold generation to students as the excellent generation in the 21st century. Evaluation to the nine collaborator teachers was measured quantitatively using evaluation tool and assessment instrument prepared which refers to the Teacher Performance Assessment Tool (APKG) and is also measured using a classical assessment of achievement through learning outcome. The results of the evaluation given to the teacher's knowledge and skills before being given training in the PDPSU activity show the participants only obtained an average score 67. Meanwhile, the teacher's knowledge and skills increased after being given training in this PDPSU activity by reaching an average score of 85. As a result, this PDPSU activity could improve the knowledge and skills of teachers in applying humanist literacy education to the content of language learning materials in the primary school level for building Pancasila-uphold generation as the excellent students in the 21st century.